Changes to medication abortion clinical practices in response to the COVID-19 pandemic - Tschann, Mary (Contraception, 2021)
OBJECTIVES: To document medication abortion clinical practice changes adopted by providers in response to the COVID-19 pandemic. STUDY DESIGN: Longitudinal descriptive study, comprised of three online surveys conducted between April to December, 2020. We recruited sites from email lists of national abortion and family planning organizations. RESULTS: Seventy-four sites opted to participate. We analyzed 55/74 sites (74%) that provided medication abortion and completed all three surveys. The total number of abortion encounters reported by the sites remained consistent throughout the study period, though medication abortion encounters increased while first-trimester aspiration abortion encounters decreased. In response to the COVID-19 pandemic, sites reduced the number of in-person visits associated with medication abortion and confirmation of successful termination. In February 2020, considered prepandemic, 39/55 sites (71%) required 2 or more patient visits for a medication abortion. By April 2020, 19/55 sites (35%) reported reducing the total number of in-person visits associated with a medication abortion. As of October 2020, 37 sites indicated newly adopting a practice of offering medication abortion follow-up with no in-person visits. CONCLUSIONS: Sites quickly adopted protocols incorporating practices that are well-supported in the literature, including forgoing Rh-testing and pre-abortion ultrasound in some circumstances and relying on patient report of symptoms or home pregnancy tests to confirm successful completion of medication abortion. Importantly, these practices reduce face-to-face interactions and the opportunity for virus transmission. Sustaining these changes even after the public health crisis is over may increase patient access to abortion, and these impacts should be evaluated in future research. IMPLICATIONS STATEMENT: Medication abortion serves a critical function in maintaining access to abortion when there are limitations to in-person clinic visits. Sites throughout the country successfully and quickly adopted protocols that reduced visits associated with the abortion, reducing in-person screenings, relying on telehealth, and implementing remote follow-up.